Accuracy of Lung Ultrasonography for Diagnosis of Heart Failure; a Systematic Review and Meta-analysis - Rahmani, Erfan; Farrokhi, Masoud; Farrokhi, Mehrdad; Nouri, Shadi; Fard, Atousa Moghadam; Hoorshad, Behnam; Abderam, Amir (Shahid Beheshti Univ Medical Sciences, 2025)
Introduction: Despite the evident impact of ultrasonography on diagnosis in acute care settings, there is still a great deal of uncertainty regarding its accuracy. This study aimed to assess the diagnostic performance of lung ultrasonography (LUS) for the identification of acute heart failure in patients with suggestive manifestations. Methods: Medline, Scopus, and Web of Science were comprehensively searched from their inception to November 2024 to identify original studies investigating accuracy of LUS for diagnosis of heart failure. Data extraction and quality assessment were performed by two independent reviewers. The statistical analysis for pooling the results of diagnostic performance parameters was conducted using Stata and Meta-DiSc softwares. Results: Thirty-eight included studies in this meta-analysis were published between 2006 and 2024, encompassing a total of 6,783 patients. There was significant heterogeneity between included studies with respect to sensitivity (I2=92.51 and P<0.01) and specificity (I2=93.79 and P<0.01). The pooled sensitivity, specificity, and accuracy of LUS for detection of heart failure were 0.92 (95% CI, 0.87-0.95), 0.90 (95% CI, 0.860.93), and 0.96 (95% CI, 0.94-0.98), respectively. In addition, pooled positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) were 7.87 (95% CI, 5.60-11.07), 0.14 (95% CI, 0.10-0.19), and 70.74 (95% CI, 41.98-119.21), respectively. Conclusion: Our meta-analysis demonstrates that LUS is a highly practical imaging for diagnosing acute heart failure, with excellent sensitivity, specificity, and accuracy. It is particularly valuable for excluding the heart failure when the result is negative. However, the influence of outlier and influential studies warrants caution, and future studies should aim to further validate these findings in diverse clinical contexts.
Keywords: Dyspnea; Heart Failure; Lung; Meta-analysis; Ultrasonography